HUBUNGAN TINGKAT KARBON DENGAN INDIKATOR EKONOMI DI ASEAN - Khoirudin, Rifki; Aufaa Mulia, Muhammad Rifki; Apriliana, Dwi (JISEF : Journal Of International Sharia Economics And Financial, 2024)
Carbon Footprint is a leading indicator that indicates the amount of area and resources needed to absorb CO2 emissions from economic and human waste to reduce industrial by-products and human-generated waste. Rapid economic growth, population increase, as well as human economic activities, have had a negative impact on the environment, characterized by an increase in carbon dioxide emissions. In recent years, ASEAN countries have faced significant carbon footprint problems. The purpose of this study is to analyse the influence of economic growth variables, exports, imports, population and energy consumption on carbon dioxide emissions. The type of data used is secondary data with panel data for the period 2012-2022. The analysis method used in this research is the Fixed Effect Model (FEM). The results of this study are that the economic growth variable has no effect on carbon dioxide emissions, then the Export, Import and Population variables have a positive and significant effect on carbon dioxide emissions. While the energy consumption variable has a negative and significant effect on carbon dioxide emissions in ASEAN countries.